Utility of the comprehensive marijuana motives questionnaire among medical cannabis patients. (January 2018) - Bohnert, Kipling M.; Bonar, Erin E.; Arnedt, J. Todd; Conroy, Deirdre A.; Walton, Maureen A.; Ilgen, Mark A.
Abstract: Background: Little is known about motives for cannabis use among the population of adults using cannabis medically. Therefore, we evaluated the performance of the 12 factor, 36-item Comprehensive Marijuana Motives Questionnaire (CMMQ) among a sample of medical cannabis patients. Methods: Study participants were adults ages 21 years or older with scheduled appointments to obtain new or renewed medical cannabis certification from clinics in one Midwestern state ( n  = 1116). Confirmatory factor analysis was used to evaluate properties of the CMMQ. Multiple regressions were used to estimate associations between motives and cannabis use, physical health functioning, and mental health functioning. Results: Fit indices were acceptable, and factor loadings ranged from 0.57 to 0.94. Based on regression analyses, motives accounted for 7% of the variance in recent cannabis use, and independent of cannabis use, accounted for 5% and 19% of physical and mental health functioning, respectively. Regression analyses also revealed that distinct motives were associated with cannabis use and physical and mental health functioning. Conclusions: Among adults seeking medical cannabis certification, the factor structure of the CMMQ was supported, and consistent with prior studies of adolescents and young adults using cannabis recreationally. Thus, individuals who use cannabis medically may have diverse reasons for use that extend beyond the management of medical symptoms. In addition, coping and sleep-related motives may be particularly salient for this population. Findings support the utility of the CMMQ in future research on medical cannabis use; however, expansion of the scale may be needed to address medical motives for use. Highlights: We examined the factor structure of the CMMQ among medical cannabis patients. We also evaluated relationships between motives and cannabis use and functioning. Findings support the utility of the CMMQ among those using cannabis medically. Adults using cannabis for medical purposes appear to have diverse reasons for use.